Acute syphilitic meningitis in an HIV-infected patient. (2018) - Wagemakers, Alex; Hepp, Dagmar; Killestein, Joep; Peferoen, Laura; Ang, Wim
Abstract: We present a case of acute syphilitic meningitis in a 28-year old HIV-infected patient, presenting with a seizure. MRI revealed a meningeal lesion with cortical involvement, and the patient described previous treatment for syphilis. Final diagnosis was established by PCR and spirochete staining on a brain biopsy, upon which the patient was successfully treated with benzylpenicillin.